The developing person through the life span - Berger, Kathleen Stassen (Worth Publishers, 2011)
"The seventh edition comes with significant revision of cognitive development throughout childhood, revised and updated chapters on adolescence, and more attention to emerging and early adulthood. It is a thorough revision with new research on everything from genetics to the timing of puberty, including brain development, life span disorders and cultural diversity. It also includes new learning features promoting critical thinking, revision and application." - Vydavatelská anotace
Předchozí vyd.: New York: Worth, 2008
Terminologický slovník
Keywords: vývojová psychologie; psychologie dítěte; vývoj dítěte; psychologie životní cesty; psychologie dospělých; developmental psychology; child psychology; child development; lifespan psychology; adult psychology; monografie; monographs